Ruthenium pincer-catalyzed cross-dehydrogenative coupling of primary alcohols with secondary alcohols under neutral conditions - Srimani, Dipankar; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2012)
Cross-dehydrogenative coupling of primary alcohols with secondary alcohols to obtain mixed esters with the liberation of molecular hydrogen is achieved in high yield and good selectivity under neutral conditions, using a bipyridyl-based PNN ruthenium(II) pincer catalyst.

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Reverse-hydroformylation: a missing reaction explored - Nandakumar, Avanashiappan; Sahoo, Manoj Kumar; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2015)
Recent progress in transition-metal catalysed acceptor- and acceptorless-reverse hydroformylation of aldehydes for the conversion of olefins has been discussed. The aldehyde feedstock serves as a source for production of syngas and valuable alkenes.

Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.

Room temperature catalytic dehydrogenation of cyclic amines with the liberation of H-2 using water as a solvent - Sahoo, Manoj K.; Balaraman, Ekambaram (Green Chemistry, 2019)
Catalytic dehydrogenation of cyclic amines, in particular partially saturated N-heterocycles to N-heterocyclic arenes, with the removal of molecular hydrogen as the sole byproduct in water is reported. This dehydrogenation reaction proceeds smoothly under very mild and benign conditions and operates at room temperature. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and a newly synthesized cobalt complex as the proton-reduction catalyst. A detailed mechanistic study (control experiments, electrochemical studies, UV-visible experiments) is presented for the present dual catalysis.

Recent advances in liquid organic hydrogen carriers: an alcohol-based hydrogen economy - Yadav, Vinita; Sivakumar, Ganesan; Gupta, Virendrakumar; Balaraman, Ekambaram (ACS Catalysis, 2021)
Energy storage and the use of abundantly available feedstock without contributing to the carbon footprint are two significant global challenges. In this regard, the development of high-performance, low-cost, sustainable, and environmentally friendly energy storage and production systems is crucial to fulfill the growing energy demands of the current society. The use of hydrogen will diversify energy sources as it significantly reduces greenhouse gas emissions and environmental pollution during energy conversion. Although the hydrogen economy is quite beneficial, hydrogen storage is still very challenging, and the existing methods suffer from a lot of problems and drawbacks. The conventional liquefaction and compression hydrogen storage technologies are associated with several challenges, including low storage density, boil-off losses, relatively high costs, and safety and transportation concerns. In recent years, liquid organic hydrogen carrier (LOHC) systems have attained a lot of importance as a substitute for the traditional storage methods. Hydrogen storage and transport using LOHCs are based on two-step cycles, such as (i) loading/storage of hydrogen by catalytic hydrogenation of H2-lean compounds and (ii) unloading/releasing hydrogen by dehydrogenating the resulting H2-rich liquids. Since alcohols are widely accessible from various industrial processes or even from biomass-derived precursors, the catalytic acceptorless dehydrogenation of alcohols is an attractive approach for future hydrogen storage applications. Hence, the catalytic dehydrogenation-hydrogenation of alcohols can be used for the development of alcohol-based LOHC systems which are economical, safe, and easy to handle. Further, they are similar to crude oils under ambient conditions and thus are suitable for use in the current energy infrastructure. This Review covers several essential aspects of these developing efficient and abundantly available LOHC systems for efficient hydrogen storage and transport applications. Additionally, reversible LOHC systems based on the catalytic dehydrogenation-hydrogenation of alcohols and their corresponding carbonyl compounds have been discussed.